f(0)=−1 f'(0)=−11 f''(0)=5 f'''(0)=8
f(x) = +......
f(x) = +......

Using the definition of a Maclaurin series,
f(x) = f(0) + f '(0) x + f ''(0) x^2/2! + f '''(0) x^3/3! + ...
.....= 1 + (11)x + 5x^2/2! + 8x^3/3! + ...
.....= 1  11x + (5/2) x^2 + (4/3) x^3 + ...
I hope this helps!
f(x) = f(0) + f '(0) x + f ''(0) x^2/2! + f '''(0) x^3/3! + ...
.....= 1 + (11)x + 5x^2/2! + 8x^3/3! + ...
.....= 1  11x + (5/2) x^2 + (4/3) x^3 + ...
I hope this helps!

Use the Maclurin formula is very simple you can do this on your own